2021
DOI: 10.1002/aoc.6331
|View full text |Cite
|
Sign up to set email alerts
|

Insights into complexation and enantioselectivity of uranyl‐2‐(2‐hydroxy‐3‐methoxyphenyl)‐9‐(2‐hydroxyphenyl)thiopyrano[3,2‐h]thiochromene‐4,7‐dione with R/S‐organophosphorus pesticides

Abstract: In order to explore the enantioselectivity of new uranyl receptors to chiral organophosphorus pesticides (COPs), we designed a novel ligand: 2‐(2‐hydroxy‐3‐methoxyphenyl)‐9‐(2‐hydroxyphenyl)thiopyrano[3,2‐h]thiochromene‐4,7‐dione (HTTDN) and constructed a new receptor of Uranyl‐HTTDN by complexation of HTTDN with uranyl. The complexation and enantioselectivity of Uranyl‐HTTDN to COPs of R/S‐methamidophos (R/S‐MAPs) and R/S‐acephates (R/S‐APs) were studied using density functional theory (DFT) method in this pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 57 publications
(48 reference statements)
0
6
0
Order By: Relevance
“…The ∆ G of the four complexes of receptor–guests was the most negative in toluene, revealing that the receptor has the strongest binding ability with R/S‐PFFs in toluene; this was also in line with our previous research results. [ 42 ] The ∆ G values of all the complexes of receptor–guests were the most negative in the gas phase, exhibiting that the binding energy of receptors with guests in the gas phase is the largest and the reaction is most likely to occur. By comparing the ∆ G values of all the complexes of receptor–guests, we found that the ∆ G of [R/S‐PFF‐Uranyl‐TMMTs] 2+ was slightly smaller than that of [R/S‐PFF‐Uranyl‐TMMOs] 2+ generally.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ∆ G of the four complexes of receptor–guests was the most negative in toluene, revealing that the receptor has the strongest binding ability with R/S‐PFFs in toluene; this was also in line with our previous research results. [ 42 ] The ∆ G values of all the complexes of receptor–guests were the most negative in the gas phase, exhibiting that the binding energy of receptors with guests in the gas phase is the largest and the reaction is most likely to occur. By comparing the ∆ G values of all the complexes of receptor–guests, we found that the ∆ G of [R/S‐PFF‐Uranyl‐TMMTs] 2+ was slightly smaller than that of [R/S‐PFF‐Uranyl‐TMMOs] 2+ generally.…”
Section: Resultsmentioning
confidence: 99%
“…[38][39][40][41] Their insecticidal mechanism is to phosphorylate the active site of acetylcholinesterase by inhibiting the acetylcholinesterase in the organism, thereby losing the ability to decompose acetylcholine. [42][43][44] R/S-Profenofos (R/S-PFFs), as shown in Figure 1, is a representative of COPs used to control many pests of cotton, fruit trees, and other crops. [45] However, different configurations of COPs have different biological toxicity, [46][47][48] and excessive use can cause great harm to the environment and humans.…”
Section: Introductionmentioning
confidence: 99%
“…However, conducting experiments is bound to be difficult and contingent, so the use of computational methods can provide the theoretical basis and alternative solutions for experimental studies and avoid many risks. 3 The design and applications of uranyl complexes have been quite extensive, such as studies employing uranyl complexes for the separation of lanthanides and actinides, [4][5][6][7][8][9] the separation of chiral enantiomers, [10][11][12][13][14][15][16] and the removal and extraction of radionuclides. [17][18][19][20] Among them, the separation of chiral enantiomers using uranyl-containing receptors is a promising and valuable study.…”
Section: Introductionmentioning
confidence: 99%
“…14 Yang et al devised Uranyl-HTTDN receptors for coordination and enantioselectivity studies of methamidophos and acephates, respectively. 16 Liu et al designed two receptors, Uranyl-TMMT and Uranyl-TMMO, to study the separation and coordination capacity for profenofos and presented good separation results. 11 Inspired by the TMMT/TMMO ligands and considering the non-polluting incineration of the ligand molecules containing only C, H, O, and N atoms, 34,35 we designed the 2-(9-[1H-pyrazole-1-carbonyl]-1,10-phenanthroline-2-yl)-1H-inden-1-one (HPIDO) ligand with o-phenanthroline as the basic skeleton and bound it to the uranyl ion to form a chiral-at-uranium complex of Uranyl-HPIDO receptor and further unraveled the binding and enantioseparation ability of Uranyl-HPIDO to R/S-MLXs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation